Genetic variation in the conjugative plasmidome of a hospital effluent multidrug resistant Escherichia coli strain. (April 2019) - Ferreira, Catarina; Bogas, Diana; Bikarolla, Santosh K.; Varela, Ana Rita; Frykholm, Karolin; Linheiro, Raquel; Nunes, Olga C.; Westerlund, Fredrik; Manaia, Célia M.
Abstract: Bacteria harboring conjugative plasmids have the potential for spreading antibiotic resistance through horizontal gene transfer. It is described that the selection and dissemination of antibiotic resistance is enhanced by stressors, like metals or antibiotics, which can occur as environmental contaminants. This study aimed at unveiling the composition of the conjugative plasmidome of a hospital effluent multidrug resistant Escherichia coli strain (H1FC54) under different mating conditions. To meet this objective, plasmid pulsed field gel electrophoresis, optical mapping analyses and DNA sequencing were used in combination with phenotype analysis. Strain H1FC54 was observed to harbor five plasmids, three of which were conjugative and two of these, pH1FC54_330 and pH1FC54_140, contained metal and antibiotic resistance genes. Transconjugants obtained in the absence or presence of tellurite (0.5 μM or 5 μM), arsenite (0.5 μM, 5 μM or 15 μM) or ceftazidime (10 mg/L) and selected in the presence of sodium azide (100 mg/L) and tetracycline (16 mg/L) presented distinct phenotypes, associated with the acquisition of different plasmid combinations, including two co-integrate plasmids, of 310 kbp and 517 kbp. The variable composition of the conjugative plasmidome, the formation of co-integrates during conjugation, as well as the transfer of non-transferable plasmids via co-integration, and the possible association between antibiotic, arsenite and tellurite tolerance was demonstrated. These evidences bring interesting insights into the comprehension of the molecular and physiological mechanisms that underlie antibiotic resistance propagation in the environment. Graphical abstract: Image 1 Highlights: Conjugative plasmidome analyzed under different conditions, e.g. tellurite or arsenite. Acquired plasmids conferred new phenotypic and genotypic resistance traits. Different plasmids and co-integrates were observed in the conjugative plasmidome. Plasmids of the replicon type HI2 were transferred more frequently than of the type FIA/FIB. Arsenite 0.5 μM favoured the transfer of plasmid of the replicon type FIA/FIB.